Maintaining osmotic balance in legume nodules - Poole, PS; Ledermann, R (Oxford University Press, 2022)
Pinitol (3-O-methyl-D-chiro-inositol) is shown to be transported passively across the plant-derived symbiosome membrane in Lotus japonicus by the energy-independent polyol transporter LjPLT11. Accumulation of pinitol is crucial to maintenance of osmotic balance in nodules. RNAi lines reduced in LjPLT11 have disrupted symbiosome membranes, reduced N2 fixation by rhizobial bacteroids and reduced plant growth. There is also an increase in production of reactive oxygen species (ROS) in LjPLT11 RNAi lines, consistent with osmotic imbalance causing increased stress in nodules.